Endocrine aspects of pre-eclampsia. Issue 1 (March 2015) - Currie, Gemma; Carty, David M.; Connell, John M.; Freel, Marie
<x xml:space="preserve">Abstract</x> Pre-eclampsia, defined as hypertension with proteinuria occurring after 20 weeks' gestation, complicates up to 8% of pregnancies and is a major contributor to perinatal morbidity and mortality worldwide. It is now widely accepted that pre-eclampsia is also associated with the risk of maternal cardiovascular disease in later life. Although the pathogenesis of this complex condition remains incompletely understood, impaired placentation and subsequent endothelial dysfunction and inflammation are among the proposed hypotheses. In recent years, there has been a resurgence of interest in the pivotal role of aldosterone and volume status in pre-eclamptic pregnancy. This review will focus on the endocrine mechanisms believed to underpin development of pre-eclampsia and its early and late complications.